AQUAPONICS AS AN ALTERNATIVE TO FULFIL TODDLER NUTRITION TO REALISE 2024 ZERO STUNTING IN WONOGIRI - Kasanah, Nur; Titis Bayumargo Utoro; Riski Saputra; Alimatuss Zhahroh (InEJ: Indonesian Engagement Journal, 2024)
Aquaponics can be an innovative alternative in fulfilling nutrition for stunted toddlers. The aquaponics system simultaneously integrates fish farming and plant growth, producing nutrient-rich agricultural products and providing fish protein. This community service activity aims to meet the nutritional intake of toddlers indicated to be stunted in Bangsri Village, Purwantoro District, Wonogiri Regency while supporting the efforts of the Wonogiri Regency Government to realize the 2024 Zero Stunting program. The service method chosen is asset-based community development (ABCD), which consists of inculturation, discovery, design, definition, and reflection activities. Data were collected through interviews, observation, and documentation. The results showed that stunting is not a representation of poverty. Stunted toddlers also exist in well-off families. From the education, facilitation, and assistance of aquaponics in families with stunted toddlers for 30 days, healthy and pesticide-free catfish and water spinach vegetables can be harvested as a source of nutrition and animal protein for stunted toddlers. It proves aquaponics positively affects the nutrition of stunted children and supports the 2024 Zero Stunting program in Wonogiri.